Risking Antimicrobial Resistance A collection of one-health studies of antibiotics and its social and health consequences - Jensen, Carsten Strøby; Nielsen, Søren Beck; Fynbo, Lars (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Antimicrobial resistance (AMR) is predicted to be one of the greatest threats to public health in the twenty-first century. In this context, understanding the reasons why perceptions of antibiotic risk differ between different groups is crucial when it comes to tackling antibiotic misuse. This innovative volume gathers together chapters written by sociologists, psychologists and linguists with the common aim of examining the social factors that affect use of antibiotics among humans and animals. A unique focus on Denmark - one of the world's most progressive countries when it comes to antibiotic regulation - as well as Europe more broadly, makes this book a valuable resource for regulatory deliberations on future antibiotic policy to effectively combat AMR.